Not for want of trying: Effort and Success of women in principles of microeconomics. (November 2020) - Hadsell, Lester
Abstract: Prior research suggests that women enter their first college-level economics class with lower expectations of success while also thinking they must work harder than men to earn similar grades. This paper examines effort (completion of optional work) and success (grades) in principles of economics, with special focus on differences between women and men. Two sets of tests are performed. One set, probit models controlling for student attributes, examines submission rates for optional online quizzes and an optional final exam; a second set uses a regression discontinuity approach to measure incentive effects of grades, examining performance on exams. Women submit more quizzes and have exam scores and course grades that are similar to men, in contrast to numerous prior studies showing a gender difference. Quizzes are identified as one potential reason for men-women exam score equivalence. Additionally, women with a B+ (just shy of an A-) before the final exam are more likely to choose to submit the optional final compared to similar men.